Rebranding a District: the Breiðholt Project in Reykjavik - Wilkinson, Catherine; Fumagalli, Ilaria; Rossetti, Silvia (TeMA - Journal of Land Use, Mobility and Environment, 2016)
Cities have gained increasing attention from government, researchers, and industry. The focus upon smarter and more efficient cities is important, but incomplete. Against this backdrop, COST Action builds on a European Science Foundation exploratory workshop on the emerging theme of smart and liveable cities. COST Action’s framework for People Friendly Cities in a Data Rich World acknowledges that the city is largely the product of top-down expertise, and a process in which the citizen plays a marginal role. Despite this top-down approach, citizens have had to build personal and collective biographies from the infrastructure of the city. This paper explores how the community of Breiðholt, Reykjavik, is being transformed from a disadvantaged suburb, characterised as a ‘ghetto’, into a thriving community where citizens play a central role in decision-making. This paper presents the outcomes of a fieldwork experience, undertaken in Breiðholt as part of COST Action’s Winter Training School, focused on the drivers behind, actions, and benefits of the Breiðholt Project and the Breiðholt Congress. In making recommendations for the Project and Congress, and other community-based initiatives, this paper encourages the sharing of best practices among different departments of the city, and to better utilise bridge makers (key stakeholders/community leaders) to build trust through face-to-face interactions with citizens.